Association between polymorphisms of glucagon-like peptide-1 receptor gene and susceptibility to osteoporosis in Chinese postmenopausal women - Xiaoxue Bao; Chang Liu; Huiming Liu; Yan Wang; Peng Xue; Yukun Li (Journal of Orthopaedic Surgery and Research)
Abstract Background The influence of the glucagon-like peptide-1 receptor (GLP-1R) on bone metabolism is well-established. However, it has been observed that single nucleotide polymorphisms (SNPs) in the GLP-1R gene can partially affect its function. Therefore, this study aims to investigate the association between SNPs in the GLP-1R gene and postmenopausal osteoporosis (PMOP) within the Chinese Han population. Methods This study employed a cross-sectional case–control design, recruiting a total of 152 participants, including 76 patients with osteoporosis (OP) (case group) and 76 healthy individuals (control group). Seven tag SNPs of GLP-1R were selected from the National Center of Biotechnology Information and Genome Variation Server. The association between GLP-1R polymorphisms and PMOP risk was assessed using different genetic models and haplotypes, while also exploring SNP-SNP and SNP-environment interactions. Results Our results showed that minor alleles A at rs3765468, A at rs3765467 and G at rs4714210 showed significant associations with an increased risk of OP. Individuals with rs3765468 AG-AA genotype and rs3765467 AG-AA genotype exhibited a significantly higher risk of PMOP. Moreover, haplotype analysis revealed a significant association of the GACACA haplotype on PMOP risk (P = 0.033). Additionally, a multiplicative interaction was observed between rs3765468 and rs3765467 that was associated with an increased risk of PMOP (P interaction  = 0.012). Conclusions Specific SNPs in the GLP-1R gene were linked to an increased risk of PMOP. This study improves our understanding of the genetic basis of PMOP in this population and suggests that genetic screening can identify individuals at risk for developing PMOP, enabling early prevention.